Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 41


x=$-\frac{1}{2}$ or $x=-\frac{2}{3}$

Work Step by Step

$6x^{2}+13x+6$ =$6x^{2}+9x+4x+6$ =$3x(2x+1)+2(2x+1)$ =$(2x+1)(3x+2)$ x=$-\frac{1}{2}$ or $x=-\frac{2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.